Distributed OSGi built over message‐oriented middleware. (8th December 2011) - Psiuk, Marek; Żmuda, Daniel; Zieliński, Krzysztof
SUMMARY This paper describes key aspects of remote service invocation in federations of OSGi containers. It refers to the OSGi Remote Service Admin specification and describes its efficient implementation over message‐oriented middleware. Scalability problems of several different approaches to implementation are identified, and a solution in a form of innovative Remote Service Admin model extension is proposed. The extension, named On‐demand Remote Service Admin, is analyzed and validated in the context of a motivating scenario. Validation includes performance and scalability evaluation, which confirms that all assumed requirements have been satisfied by the constructed prototype. Finally, the presented research is compared with related works. Copyright © 2011 John Wiley & Sons, Ltd.